Long‐Term Operation of Nb‐Coated Stainless Steel Bipolar Plates for Proton Exchange Membrane Water Electrolyzers. Issue 8 (3rd June 2022) - Stiber, Svenja; Hehemann, Michael; Carmo, Marcelo; Müller, Martin; Ayers, Katherine E.; Capuano, Christopher; Danilovic, Nemanja; Morawietz, Tobias; Biswas, Indro; Gazdzicki, Pawel; Heger, Jan‐Frederik; Gago, Aldo Saul; et al.
Abstract : Proton exchange membrane water electrolysis (PEMWE) is the most promising technology for green hydrogen production using renewable electricity, but it is expensive due to the Ti bipolar plates (BPPs). Herein, a PEMWE stack with coated stainless steel (ss) BPPs (Nb/Ti/ss‐BPP and Nb/ss‐BPP) is reported, which operates for about 14 000 h at 1.63 ± 0.12 A cm −2 and 65 °C. The average degradation rate is as low as 1.2% or 5.5 μV h −1 . Scanning electrode microcopy reveals no signs of corrosion of the ss beneath the coatings. The interfacial contact resistance increases due to the formation of poorly conductive amorphous Nb oxides, as shown by atomic force microscopy and X‐Ray photoelectron spectroscopy, although it does not affect the cell performance. The results prove that Ti is not needed anymore as base material for manufacturing the BPPs, thus the cost of PEMWE can be significantly reduced. Abstract : Stainless steel (ss) bipolar plates (BPP) coated with Nb/Ti and Nb for proton exchange membrane water electrolysis (PEMWE) are tested in a commercial stack for almost 14 000 h. No signs of corrosion of the ss substrate can be detected, indicating that ss is a real alternative to pure Ti BPPs contributing to a significant cost reduction of the PEMWE technology.